A convergent fabrication of pH and redox dual-responsive hybrids of mesoporous silica nanoparticles for the treatment of breast cancer. Issue 2 (22nd January 2023) - Zhu, Limin; Wang, Shuangyan
Abstract: Mesoporous silica nanoparticle (MSN), sodium hyaluronate (SH), silk fibroin (SS), and oxidized sodium carboxymethyl cellulose (O-CMC) hybrids were used to develop an intelligent drug delivery platform that may be employed for pH and redox-responsive bi-drug administration. The first drug, cytarabine (Cyt), was loaded with amino-functionalized mesoporous silica (MSN-NH2 ) encased by the hydrogel of cystamine (Cys) and SH cross-linked by amide bonds. Hydrophobic doxorubicin (DOX) was co-loaded with Cyt/MSN-NH2 /SA in the hydrogel of SS and O-CMC in the Cyt- loaded hydrogel. Dual-responsive drug delivery may be achieved by encapsulating SS and O-CMC in a hydrogel, including Cyt/MSN-NH2 /SA/DOX/SS/O-CMC, which has acyl hydrazone bonds (-HC = N) and disulfide bond (-S-S-) exchange reaction with glutathione (GSH). Compared to hydrogels encapsulating only one drug (Cyt or DOX), cell survival analysis revealed that the newly fabricated hydrogels have significantly greater chemotherapeutic efficacy. The cell proliferation of the fabricated nanoparticles was examined in MCF-7 and MDA-MB-231 cells, which indicates that the nanoparticles effectively kill the cancer cells without affecting non-cancerous cells. Further, we effectively investigated the morphological changes, and various biochemical staining methods examined nuclear fragmentation/condensation. Furthermore, the biosafety of the nanoparticles was investigated by the in vivo animal model, which reveals that they remarkably enhanced the safety profile in various organs. These outcomes demonstrated that this nanoparticle platform was a promising beneficial agent for improving breast cancer treatment.